TEACHING TIME BY USING REALIA TO THE EIGHT GRADE STUDENTS OF SMP PTI PALEMBANG - Inggrid Inggrid; Retika Wista Anggraini (Universitas Indo Global Mandiri, 2016)
The main problem of this study was the effective to teach time by using realia to the eighth grade students of SMP PTI Palembang. The objective of this study was to find out whether or not it is effective to teach time by using realia to the eight grade students of SMP PTI Palembang. This study used the quasi-experimental method. The written test was used to collect the data and it was analyzed by using mathched t- test. The population of this study was all the three grade of SMP PTI Palembang in the academic year of 2013/2014. The sample of the study was taken from the population cluster random sampling. Based on the result on the study, it was found that was effective to teach time by using realia to the eight grade of SMP PTI Palembang. The average score of the students in the post-test of the experimental group was 88,13. Meanwhile, the average score in the post-test control group was 85,37. In short, Ha was accepted than Ho. On the other hand, the use of realia is an effective way to teach time to the eight grade students of SMP PTI Palembang. Key words : using realia, quasi experimental method, population.